Use of whole-exome sequencing to identify novel monogenic gene mutations and genotype–phenotype correlations in Chinese Han children with urolithiasis - Wang, Zhi; He, Tianqu; liu, Li; Tong, Fangyun; Li, Chuangye; Zhao, Yaowang; Li, Yanfang (Frontiers in Genetics, 2023)
The incidence of urolithiasis (UL) in children has been increasing. Although the pathogenesis of pediatric UL is controversial and remains unclear, multiple monogenic causes of UL have been identified. We aim to investigate the prevalence of inherited UL causes and explore the genotype–phenotype correlation in a Chinese pediatric group. In this study, we analyzed the DNA of 82 pediatric UL patients using exome sequencing (ES). The data of metabolic evaluation and genomic sequencing were subsequently analyzed together. We detected 54 genetic mutations in 12 of 30 UL-related genes. A total of 15 detected variants were described as pathogenic mutations, and 12 mutations were considered likely pathogenic. Molecular diagnoses were made in 21 patients with pathogenic or likely pathogenic variants. Six novel mutations that were not previously reported were identified in this cohort. Calcium oxalate stones were detected in 88.9% cases (8/9) with hyperoxaluria-related mutations, while 80% of individuals (4/5) with cystinuria-causing defects were diagnosed with cystine stones. Our study highlights the significant genetic abnormalities in pediatric UL and demonstrates the diagnostic power of ES for screening patients with UL.